The Community Structure of Macrozoobenthic Associated with Seagrass on Sandy Bottom in Jepara - Ruswahyuni Ruswahyuni (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2008)
Macrozoobenthos play an importan role in food chain stucture within coastal ecosystem. As benthic organisms their life are highly influenced by surrounding environment including as physical, chemical anf biological factors. Sea grass is a macrophyte community that serves as habitat for macrozoobenthos. The result of observation showed that the most abundant macrozoobenthos living in seagrass at Bandengan and Pulau Panjang was Polychaeta. In addition, the abundance of macrozoobenthos in seagrass increased with the increase of seagrass density. Keywords: Benthic, seagrass, community structure